Tinjauan Putusan Pengadilan Militer Bandung Nomor 196-K/PM.II- 09/AD/XII/2021 bagi Anggota Militer yang Melakukan Tindak Pidana Berulang - Andayani, Lily; Ikrardini, Zulfika (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
In military criminal law, a service member who commits a repeated criminal offense (recidivist) may be subject to an additional penalty in the form of dishonorable discharge from military service. This sanction is based on military interests, as the member is deemed no longer beneficial or representative of the Indonesian National Armed Forces (TNI) or the public, considering their history of repeated criminal acts. However, in Judge's Verdict Number 196-K/PM.II-09/AD/XII/2021 of the Military Court II-09 Bandung, the defendant, a ten-time recidivist, was not subjected to the additional penalty of military discharge by the Panel of Judges. This research employs a normative juridical approach using document study for data collection and a normative qualitative analysis method, involving an in-depth analysis of the Judge's Verdict and the positive legal provisions in Indonesia. The findings conclude that the considerations given by the Panel of Judges in the said verdict failed to provide a proportional balance between legal interests, public interests, and military interests. The author argues that the Panel of Judges should have imposed the additional penalty of discharge from military service on the Defendant, as their actions are deemed to have a negative impact on the life order and value system within the TNI, such as the Sapta Marga (Seven Pledges), Delapan Wajib TNI (Eight TNI Obligations), Soldier's Oath, and other military foundations.